Interpersonal communication skills of nurse managers and nursing performance - Ibrahim, Yuliani; Ahamat, Amiruddin (Universiti Utara Malaysia, 2019)
Interpersonal communication between the nurse manager and the executing nurse is needed for the continuity and productivity of the profession, whereby one’s productivity is strongly influenced by performance. Therefore, this study aims to know the extent of the relationship between the interpersonal communication skills (leadership, communication process, motivation, and negotiation skills) of the nurse managers, (independent variable), and the performance of nurses, (dependent variable) at Tgk. Chik Ditiro Sigli Hospital and Harapan Bunda Banda Aceh Hospital in Indonesia. The population in this study were all nurses at the two hospitals consisting of 331 respondents. The results showed a significant relationship between the interpersonal communication skills of the nurse managers and the performance of the nurses at the two hospitals. The test results also showed that there was a significant difference between the interpersonal communication skills of the nurse managers and the performance of nurses at Tgk. Chik Ditiro Sigli Hospital and at Harapan Bunda Banda Aceh Hospital. The only variable that showed similarities between the two hospitals was motivation.